Implementation of the Lex Certa Principle towards the Ambiguity of Digital Law's in Indonesia - Haritjahjono, Budi; Sodikin, Sodikin (Universitas Muhammadiyah Purworejo, 2025)
Ambiguity in Indonesia's digital laws, particularly in the Electronic Information and Transactions Law (ITE’s Law), has raised concerns over the criminalization of free expression and the erosion of digital rights. Vague terms like